Self-Efficacy Boosts Online Accounting Learning in Indonesia: Efikasi Diri Dorong Pembelajaran Akuntansi Daring di Indonesia - Rokhillah, Yuni; Biduri, Sarwenda (Indonesian Journal of Education Methods Development, 2024)
This research investigates the impact of online lectures, learning methods, and learning motivation on accounting students' comprehension during COVID-19, using self-efficacy as a moderating variable. The study employs a quantitative approach with data from 155 accounting students at Universitas Muhammadiyah Sidoarjo, collected via questionnaires and analyzed using SmartPLS. Results show that online lectures, diverse learning methods, and learning motivation significantly enhance understanding of accounting subjects, with self-efficacy moderating these effects. These findings suggest that boosting self-efficacy can improve the effectiveness of online learning and teaching methods. Highlights: Learning Impact: Online lectures enhance accounting comprehension. Moderation: Self-efficacy moderates the learning effects. Implication: Boosting self-efficacy improves online learning outcomes. Keywords: Online lectures, learning methods, learning motivation, self-efficacy, accounting comprehension